HUBUNGAN PERAN KELUARGA DENGAN KEPATUHAN DIET PADA PASIEN DIABETES MELITUS TIPE 2 DI RS HORAS INSANI PEMATANG SIANTAR TAHUN 2023 - Sihombing, Dewita; Rostime Hermayerni Simanulang (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Compliance with the diet of type 2 diabetes mellitus sufferers is one of the important things in management because sufferers often do not pay attention to balanced food intake. A good family role will influence the implementation of the diabetes mellitus treatment program undertaken by the patient. The aim of the research is to determine the relationship between family roles and dietary compliance in type 2 diabetes mellitus patients. The research design is an analytical survey that tries to explore how and why this phenomenon occurs. Then carry out a dynamic analysis of the correlation between phenomena, both between risk factors and effect factors. This research uses a cross sectional approach, namely a research design by taking measurements at the same time. The total population for this study was all 104 diabetes patients hospitalized at Horas Insani Pematang Siantar Hospital. Sampling was taken using a purposive sampling technique, namely determining samples with certain considerations, meaning that each subject taken from the population was chosen deliberately based on certain objectives and considerations, the number of samples required was 51 respondents. The instrument used was a questionnaire sheet while testing was carried out using the Pearson Product Moment test because the data distribution did not have a normal distribution, namely <0.05. The conclusion of this research is that there is a relationship between the role of the family and dietary compliance in patients with type 2 diabetes mellitus at Horas Insani Pematang Siantar Hospital with a p value of 0.001. Suggestions for future researchers can be used as basic reference material for conducting further research regarding the relationship to controlling diabetes mellitus and can conduct research with different variables such as family support, level of knowledge, the role of health workers and self-motivation.